ANALISIS PERBANDINGAN DEBIT MENGGUNAKAN METODE MANNING DAN CHEZY PADA SALURAN SEKUNDER IRIGASI PELAMBIK KECAMATAN PRAYA BARAT DAYA KABUPATEN LOMBOK TENGAH: Comparative Analysis Of Discharge Using The Manning And Chezy Methods In The Pelambik Irrigation Secondary Channel, Praya Barat Daya District, Central Lombok Regency - Yamin, Muhamad (Ganec Swara, 2025)
The most common empirical methods used when calculating discharge in open channels are the Manning and Chezy methods. Both methods have individual advantages and limitations. This depends on the characteristics of the channel, such as the shape of the cross-section, the roughness of the channel walls, and the gradient of the channel bed. This study is quantitative comparative with a field study approach and mathematical analysis, and is located in the Pelambik Irrigation Secondary Channel. The Manning method water discharge (Q) = 1.727 m3/sec, while the Chezy method (Q) = 1.654 m3/sec. Manning produces a slightly larger discharge compared to the Chezy method, this occurs because the Manning formula accommodates the roughness effect in more detail than Chezy. Both methods have advantages and disadvantages, Manning for accurate calculations, flexible for various types of channels, the disadvantage is that it requires a table of the right n coefficient values, while Chezy has the advantage of being simple and fast to use, the disadvantage is that the C value is difficult to determine if there is no data